Definitions, measurements and prevalence of fear of childbirth: a systematic review - C. Nilsson; E. Hessman; H. Sjöblom; A. Dencker; E. Jangsten; M. Mollberg; H. Patel; C. Sparud-Lundin; H. Wigert; C. Begley (BMC, 2018)
Abstract Background Fear of Childbirth (FOC) is a common problem affecting women's health and wellbeing, and a common reason for requesting caesarean section. The aims of this review were to summarise published research on prevalence of FOC in childbearing women and how it is defined and measured during pregnancy and postpartum, and to search for useful measures of FOC, for research as well as for clinical settings. Methods Five bibliographic databases in March 2015 were searched for published research on FOC, using a protocol agreed a priori. The quality of selected studies was assessed independently by pairs of authors. Prevalence data, definitions and methods of measurement were extracted independently from each included study by pairs of authors. Finally, some of the country rates were combined and compared. Results In total, 12,188 citations were identified and screened by title and abstract; 11,698 were excluded and full-text of 490 assessed for analysis. Of these, 466 were excluded leaving 24 papers included in the review, presenting prevalence of FOC from nine countries in Europe, Australia, Canada and the United States. Various definitions and measurements of FOC were used. The most frequently-used scale was the W-DEQ with various cut-off points describing moderate, severe/intense and extreme/phobic fear. Different 3-, 4-, and 5/6 point scales and visual analogue scales were also used. Country rates (as measured by seven studies using W-DEQ with ≥85 cut-off point) varied from 6.3 to 14.8%, a significant difference (chi-square = 104.44, d.f. = 6, p < 0.0001). Conclusions Rates of severe FOC, measured in the same way, varied in different countries. Reasons why FOC might differ are unknown, and further research is necessary. Future studies on FOC should use the W-DEQ tool with a cut-off point of ≥85, or a more thoroughly tested version of the FOBS scale, or a three-point scale measurement of FOC using a single question as 'Are you afraid about the birth?' In this way, valid comparisons in research can be made. Moreover, validation of a clinical tool that is more focussed on FOC alone, and easier than the longer W-DEQ, for women to fill in and clinicians to administer, is required.